The σ Subunit-Remodeling Factors: An Emerging Paradigms of Transcription Regulation - Vishwakarma, Rishi Kishore; Brodolin, Konstantin (Frontiers in Microbiology, 2020)
Transcription initiation is a key checkpoint and highly regulated step of gene expression. The sigma subunit of RNA polymerase (RNAP) controls all transcription initiation steps, from recognition of the -10/-35 promoter elements, upon formation of the “closed” promoter complex (RPc), to stabilization of the “open” promoter complex (RPo) and stimulation of the primary steps in RNA synthesis. The canonical mechanism to regulate sigma activity upon transcription initiation relies on activators that recognize specific DNA motifs and recruit RNAP to promoters. This mini-review describes an emerging group of transcriptional regulators that form a complex with sigma or/and RNAP prior to promoter binding, remodel the sigma subunit conformation, and thus modify RNAP activity. Such strategy is widely used by bacteriophages to appropriate the host RNAP. Recent findings on RNAP-binding protein A (RbpA) from Mycobacterium tuberculosis and Crl from Escherichia coli suggest that activator-driven changes in sigma conformation can be a widespread regulatory mechanism in bacteria.